Thermoplastic resin composition and molded body

KR103013472B1Active Publication Date: 2026-09-02아티엔스가부시키가이샤 +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020237044632
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-07
Filing Date
2022-03-30
Publication Date
2026-09-02
Estimated Expiration
2042-03-30

Smart Images

  • Figure 112023144686907-PCT00001
    Figure 112023144686907-PCT00001
  • Figure 112023144686907-PCT00002
    Figure 112023144686907-PCT00002
  • Figure 112023144686907-PCT00003
    Figure 112023144686907-PCT00003
Patent Text Reader

Abstract

Even when using recycled carbon fibers, a thermoplastic resin composition and a molded article comprising recycled carbon fibers having excellent productivity and excellent impact resistance are provided. Such a thermoplastic resin composition contains recycled carbon fibers (A) and a thermoplastic resin (B), and according to one embodiment, the thermoplastic resin composition has an oxygen content of 5.0 mass% or more of recycled carbon fibers (A), and the thermoplastic resin (B) has an average solubility parameter of 10 to 15 and also includes a polyamide resin (iB).
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a thermoplastic resin composition containing recycled carbon fibers and a molded article using the same. Background Technology

[0002] Carbon fiber reinforced plastic (hereinafter referred to as “CFRP”) reinforced by carbon fiber (hereinafter referred to as “CF”) is used in a wide range of fields, including industrial products such as sports equipment and aircraft parts. Wind turbine blades, which have traditionally used glass fiber composite materials, are being replaced with lightweight and high-strength CFRP to achieve improved efficiency and larger sizes.

[0003] Used CFRP waste or end materials (prepreg, sheet molding compound, etc.) generated during the manufacturing process of CFRP have conventionally been disposed of in landfills after crushing, but a technology has been proposed to reuse them as recycled carbon fiber (hereinafter referred to as “r-CF”).

[0004] Patent Document 1 discloses a method for recovering r-CF, comprising crushing CFRP into a scale form and then dry distilling it in a temperature range of 300 to 1,000°C under a substantially non-oxidizing atmosphere, and a method for dry distilling the CFRP in a temperature range of 300 to 1,000°C under a substantially non-oxidizing atmosphere and then crushing it into a scale form. Additionally, Patent Document 2 discloses a method for obtaining r-CF from a carbon fiber reinforced resin (CFRP) comprising CF and a matrix resin, wherein the matrix resin is pyrolyzed by heating the carbon fiber reinforced resin to obtain a heat-treated product having a resin residue content ratio of 0.01 to 30.0 mass%, and the heat-treated product is cut.

[0005] However, r-CF has poor compatibility with plastics and is not stable when mixed into resin, so recycled carbon fiber reinforced plastic reinforced with r-CF (hereinafter referred to as “r-CFRP”) has problems with productivity and mechanical strength.

[0006] Regarding such problems, Patent Document 3 discloses a resin composition obtained using a resin and recycled carbon fibers having a fiber length variation coefficient of 20% or more and not containing a sizing agent. However, the physical properties of the r-CFRP obtained by this technique were insufficient. Additionally, Patent Document 4 discloses a polyolefin resin composition comprising recycled carbon fibers, a polyolefin resin, and a dispersant having a basic group. The recycled carbon fibers have an average fiber length of 0.05 to 15.0 mm, and the amount of recycled carbon fibers is 1 to 50 mass% of the thermoplastic resin composition, with a total mass of 100 mass%. However, the market requires the development of r-CFRPs with high physical properties using resins other than polyolefins. Prior art literature

[0007] Japanese Patent Publication No. Hei 7-118440, Japanese Patent Publication No. 2020-075493, Japanese Patent Publication No. 2019-163354, Japanese Patent Publication No. 2020-176244 The problem to be solved

[0008] In the case of parts for automobiles or aircraft where safety is critical, there is a large amount of intermediate material generated during the CFRP manufacturing process. Furthermore, not only is the demand for CFRP expanding, but the lifespan of CFRP in aircraft parts and other applications is approximately 20 years, so the amount of CFRP waste is expected to increase in the future. For this reason, there is an urgent need to develop r-CFRP with excellent properties using recycled carbon fiber (hereinafter referred to as “r-CF”) recovered from CFRP waste.

[0009] The present invention has been made in consideration of the above background and aims to provide a thermoplastic resin composition and a molded article comprising recycled carbon fibers that have excellent productivity and excellent impact resistance even when recycled carbon fibers are used. means of solving the problem

[0010] After repeated diligent examinations, the inventors discovered that the problem of the present invention can be solved in the following embodiments, and thus completed the present invention.

[0011] [1]: A thermoplastic resin composition for carbon fiber reinforcement containing recycled carbon fiber (A) and thermoplastic resin (B),

[0012] The oxygen content in the recycled carbon fiber (A) is 5.0 mass% or more, and

[0013] Satisfying any one of (i) to (iv) below,

[0014] (i): The thermoplastic resin (B) has an average solubility parameter of 10 to 15 and also comprises a polyamide resin (iB),

[0015] (ii): The thermoplastic resin (B) has an average solubility parameter of 9 to 15 and also comprises at least one of an acrylic resin (ii-B1) and a styrene resin (ii-B2), wherein the acrylic resin (ii-B1) and the styrene resin (ii-B2) have a glass transition temperature of 0°C or higher.

[0016] (iii): The acid value of the recycled carbon fiber (A) is 0.002 to 0.080 mmol / g, and the thermoplastic resin (B) has an average flow onset temperature of 250°C or less, and also comprises at least one of a polyester resin (iii-B1) and a polycarbonate resin (iii-B2).

[0017] (iv): The thermoplastic resin (B) comprises a polyolefin resin having a melting point of 100°C or higher (except in the case of an acid-modified thermoplastic resin) (iv-B), at least one of an acid-modified polypropylene (iv-b-1) and a thermoplastic elastomer (iv-b-2), wherein the melting point of the acid-modified polypropylene (iv-b-1) is 130°C or higher,

[0018] However, the above oxygen content is a value obtained when measuring using an energy-dispersive X-ray spectrometer attached to a scanning electron microscope (SEM) at an acceleration voltage of 15 kV and a field of view magnification of 3000x.

[0019] The above average solubility parameter is given by the following equation (1):

[0020] SP value=√(Ev / v)=√(ΣΔei / ΣΔvi)

[0021] (wherein, Ev: evaporation energy (cal / mol), v: molar volume (cm²) 3 It is a value calculated by / mol), Δei: evaporation energy of each atom or atomic group, and Δvi: molar volume of each atom or atomic group, and

[0022] A thermoplastic resin composition, wherein the above flow initiation temperature is a temperature at which the melt viscosity of the thermoplastic resin becomes 4800 Pa·s or less under a pressure of 9.8 MPa in the evaluation of melt viscosity by a flow tester.

[0023] [2]: A thermoplastic resin composition described in [1] characterized in that the ratio of the diffraction intensity (I1) at the Bragg angle 2θ=25° and the diffraction intensity (I2) at 2θ=44° observed by X-ray diffraction of a regenerated carbon fiber (A) is less than 6.

[0024] [3]: A thermoplastic resin composition described in [1] or [2], characterized in that the bulk density of the recycled carbon fiber (A) is 0.03 to 1.0 g / cm³, provided that the bulk density is a value obtained in accordance with JIS K5101.

[0025] [4]: Satisfying (iv), acid-modified polypropylene (iv-b-1) is at 220°C, shear rate 1.2×10 3 sec -1 The melting viscosity (ηc) at A thermoplastic resin composition described in any one of [1] to [3], characterized by having a strength of 10 to 500 Pa·s.

[0026] [5]: A thermoplastic resin composition described in any one of [1] to [4], characterized in that the polyolefin resin (iv-B) satisfying (iv) and having a melting point of 100°C or higher (except in cases where it is an acid-modified thermoplastic resin) is a homopolymer of polypropylene.

[0027] [6]: A thermoplastic resin composition satisfying (iv), wherein the thermoplastic resin (B) comprises acid-modified polypropylene (iv-b-1) and a thermoplastic elastomer (iv-b-2), as described in any one of [1] to [5].

[0028] [7]: A thermoplastic resin composition described in any one of [1] to [3], satisfying any one of (i) to (iii), wherein the thermoplastic resin (B) comprises an acid-modified thermoplastic elastomer (b-1).

[0029] [8]: A molded body formed by molding from a thermoplastic resin composition described in any one of [1] to [7]. Effects of the invention

[0030] According to the present invention, even when recycled carbon fibers are used, it is possible to provide a thermoplastic resin composition and a molded article comprising recycled carbon fibers that have excellent productivity and excellent impact resistance, exhibiting excellent effects. Specific details for implementing the invention

[0031] Hereinafter, an example of a thermoplastic resin composition and a molded article of the present disclosure is described. Furthermore, other embodiments are also included within the scope of the present invention insofar as they are consistent with the spirit of the present invention. Additionally, numerical ranges specified using “to” in this specification include numerical values ​​described before and after “to”. Furthermore, in this specification, recycled carbon fibers are distinguished as r-CF and carbon fibers (i.e., non-recycled carbon fibers) as CF; additionally, recycled carbon fiber reinforced plastic is referred to as r-CFRP and carbon fiber reinforced plastic (i.e., non-recycled carbon fiber reinforced plastic) is referred to as CFRP. “Film” and “sheet” are not distinguished by thickness. Furthermore, unless specifically annotated, various components appearing in this specification may each be used independently as a single type or in combination of two or more types. Additionally, numerical values ​​specified in this specification are values ​​obtained by the method disclosed in the examples. In addition, “(meth)acryl” means “acrylic and / or methacrylate,” and “(meth)acrylate” means “acrylate and / or methacrylate.”

[0032] In addition, in this specification, the oxygen content refers to the value obtained when measuring using an energy-dispersive X-ray spectrometer attached to a scanning electron microscope (SEM) at an acceleration voltage of 15 kV and a field of view magnification of 3000x.

[0033] In addition, the average solubility parameter is given by the following equation (1):

[0034] SP value=√(Ev / v)=√(ΣΔei / ΣΔvi)

[0035] (wherein, Ev: evaporation energy (cal / mol), v: molar volume (cm²) 3 It is a value calculated by Δei: evaporation energy of each atom or group of atoms, Δvi: molar volume of each atom or group of atoms).

[0036] In addition, the flow initiation temperature is the temperature at which the melt viscosity of the thermoplastic resin becomes 4800 Pa·s or less under a pressure of 9.8 MPa in the evaluation of melt viscosity by a flow tester.

[0037] 1. First embodiment

[0038] 1-1. Thermoplastic resin composition

[0039] The thermoplastic resin composition for reinforcing carbon fibers according to the first embodiment (hereinafter also referred to as the composition in the first embodiment) comprises a regenerated carbon fiber (A) (hereinafter also referred to as r-CF(A)) and a thermoplastic resin (B). r-CF(A) is used in which the oxygen content in r-CF(A) is 5.0 mass% or more, and the thermoplastic resin (B) has an average solubility parameter in the range of 10 to 15. As a result of repeated diligent investigations by the inventors, it was found that by combining r-CF(A) with an oxygen content of 5.0 mass% or more and a thermoplastic resin (B) with an average solubility parameter of 10 to 15, the compatibility between the resin and the regenerated carbon fiber is significantly improved, and the adhesion between the resin and the regenerated carbon fiber can be improved.

[0040] According to the present composition, impact strength, productivity, and elastic modulus are improved. Furthermore, due to the excellent compatibility between the resin and the recycled carbon fiber, deposits on the die of the manufacturing equipment can be suppressed. By suppressing deposits, problems such as deposits being mixed into the product or deposits clogging the die holes and causing material ejection failures can be prevented, thereby increasing productivity. In addition, as the adhesion between the thermoplastic resin (B) and r-CF (A) increases, the elastic modulus can be increased. As a result, it is expected that parts that have previously used metal materials can be replaced with r-CFRP, which has excellent lightweight properties. Each component will be described in detail below.

[0041] 1-1a. Regenerated carbon fiber (A)

[0042] r-CF (recycled carbon fiber) is carbon fiber recovered by recycling single pieces of CFRP (carbon fiber reinforced plastic) or CFRP waste. The CFRP serving as the raw material for r-CF comprises CF (carbon fiber) and a matrix resin, and includes not only finished products but also pre-molded intermediate products (prepreg, towpreg, sheet molding compound, stampable sheet, bulk molding compound, etc.). Furthermore, the shape of the CFRP and the form of the included CF are not particularly limited. Thermosetting resins, thermoplastic resins, etc., are used as the matrix resin for the CFRP.

[0043] r-CF(A) of the first embodiment has an oxygen content of 5.0 mass% or more. The oxygen content in this specification refers to a value obtained by measurement as described in the examples described below. The content of other elements is also obtained by the same method. r-CF(A) is a carbon fiber obtained by thermally decomposing (gasification, carbonization, etc.) a matrix resin by heat treating and / or heat steam treating materials such as single materials or CFRP waste materials as described above. By adjusting the oxidizing atmosphere during the heating process, r-CF(A) with an oxygen content of 5.0 mass% or more can be obtained.

[0044] By combining a thermoplastic resin (B) having an average solubility parameter of 10 to 15 as described below with r-CF (A) having an oxygen content of 5.0 mass% or more, the compatibility between them can be significantly increased. It is preferable that the upper limit of the oxygen content of r-CF (A) be 20.0 mass% or less in order to maintain good strength of the thermoplastic resin composition. A more preferred range is 5.0 to 15.0 mass%.

[0045] The carbon content of r-CF(A) is 95.0 mass% or less. In order to maintain good strength of the thermoplastic resin composition containing r-CF(A), it is preferable that the lower limit of the carbon content of r-CF(A) be 80 mass% or more. In addition, other elements such as nitrogen, silicon, sodium, and sulfur may be included in r-CF(A) within a range that does not affect the effects of the present invention.

[0046] The fiber length of r-CF(A) is preferably 0.05 mm or longer to increase impact resistance and elastic modulus. The upper limit is not specifically limited, but considering ease of availability, it is preferably 20 mm or less.

[0047] Examples of commercially available r-CF(A) include the CARBISO MF series (average fiber length 0.08 to 0.1 mm, oxygen content 6%) and the CARBISO C series (average fiber length 3 to 10 mm, oxygen content 5%).

[0048] In terms of improving the adhesion between r-CF (A) and the thermoplastic resin (B), the ratio (I1 / I2) of the diffraction intensity (I1) at a Bragg angle 2θ=25° and the diffraction intensity (I2) at 2θ=44° observed by X-ray diffraction of r-CF (A) is 6 It is desirable to keep it below 25°. 2θ=25° of r-CF(A) represents the diffraction of the (002) plane, and 44° represents the diffraction of the (10) plane.

[0049] In the heat treatment process of the manufacturing process for reuse from CFRP, oxygen-derived functional groups are generated on a portion of the surface of r-CF(A) by creating an oxidizing atmosphere. With the introduction of these oxygen-derived functional groups, the diffraction intensity of the (002) plane of r-CF(A) is reduced. By reducing the diffraction intensity of the (002) plane of r-CF(A), adhesion to a thermoplastic resin (B) having an average solubility parameter of 10 to 15 can be improved. Meanwhile, considering the mechanical strength of the obtained thermoplastic resin composition, it is desirable that the diffraction intensity of the (10) plane of r-CF(A) be as high as possible. The lower limit of the strength ratio (I1 / I2) is preferably 3 or higher in terms of achieving excellent mechanical strength in the obtained thermoplastic resin composition. A more preferred range for the strength ratio (I1 / I2) is 3 to 5.9, and an even more preferred range is 4 to 5.9. In addition, the analytical intensity of I2 is preferably 500 to 1000, and more preferably 600 to 900. By adjusting the processing time under an oxidizing atmosphere, the intensity ratio (I1 / I2) of the diffraction intensity (I1) at a Bragg angle 2θ=25° and the diffraction intensity (I2) at 2θ=44° observed by X-ray diffraction is You can obtain r-CF(A) less than 6.

[0050] From the perspective of further increasing the productivity of the present composition, it is preferable that the bulk density of r-CF(A) be 0.03 to 1.0 g / cm³. By using r-CF(A) with a bulk density in this range, productivity can be increased by effectively suppressing the retention of fibers in the feed port when supplying r-CF(A) to the production facility during the manufacture of the present composition. A more suitable range for the bulk density of r-CF(A) is 0.05 to 1.0 g / cm³, and further The preferred range is 0.1 to 1.0 g / cm³. By adjusting the rotational speed of the grinder blades or the mesh size of the classification mesh, r-CF(A) with a bulk density of 0.05 to 1.0 g / cm³ can be obtained.

[0051] The amount of r-CF(A) is preferably 10 to 40 mass% of the 100 mass% of the composition, more preferably 15 to 35 mass%, and even more preferably 20 to 30 mass%, in order to achieve compatibility of mechanical properties, processability, and productivity.

[0052] 1-1b. Thermoplastic resin (B)

[0053] A thermoplastic resin is a resin that softens and becomes plastic when heated to a suitable temperature, and solidifies when cooled. The thermoplastic resin (B) according to the first embodiment refers to a resin having an average solubility parameter of 10 to 15. One type of thermoplastic resin (B) or two or more types may be used in combination. When two or more types are used, the solubility parameter of each thermoplastic resin does not need to be in the range of 10 to 15, but the average solubility parameter when the thermoplastic resins are blended needs to be in the range of 10 to 15.

[0054] In this specification, the average solubility parameter refers to a value calculated by Fedor's method and obtained by the method described in the examples below. By combining a thermoplastic resin (B) having an average solubility parameter of 10 to 15 with r-CF (A) having an oxygen content of 5.0 mass% or more, as described above, the compatibility between r-CF (A) and the thermoplastic resin (B) can be significantly increased and adhesion can be improved. As a result, impact resistance can be increased. A more preferred range for the solubility parameter of the thermoplastic resin (B) is 11 to 14.

[0055] The thermoplastic resin (B) is not particularly limited as long as the average solubility parameter is 10 to 15, and various options are available. Examples of thermoplastic resins with a solubility parameter of 10 to 15 include polyamide resin, methyl acrylate, polyacrylonitrile, and polyester resin.

[0056] Suitable examples of the present composition include a thermoplastic resin composition containing a regenerated carbon fiber (A) having an oxygen content of 5.0 mass% or more and a thermoplastic resin (B) having an average solubility parameter of 10 to 15 and also containing a polyamide resin (iB).

[0057] As specific examples of the above polyamide resins, -[NH(CH2)5CO]-, -[NH(CH2)]6NHCO(CH2)4CO]-, -[NH(CH2)6NHCO(CH2)8CO]-, -[NH(CH2) 10 CO]-, -[NH(CH2) 11 A polyamide resin having at least one structural unit selected from the group consisting of [CO]-, and -[NH(CH2)2NHCO-D-CO]- (wherein D represents an unsaturated hydrocarbon having 3 to 4 carbon atoms) is preferably used. Specific examples include 6-nylon, 66-nylon, 610-nylon, 11-nylon, 12-nylon, 6 / 66 copolymer nylon, 6 / 610 copolymer nylon, 6 / 11 copolymer nylon, 6 / 12 copolymer nylon, 6 / 66 / 11 copolymer nylon, 6 / 66 / 12 copolymer nylon, 6 / 66 / 11 / 12 copolymer nylon, 6 / 66 / 610 / 11 / 12 copolymer nylon, and dimer acid-based polyamide resins. These polymers or copolymers may be alone or a mixture of two or more types.

[0058] Specific examples of the above 6-nylon resins include Amylan CM1041-LO (Toray product, MFR: 21g / 10min), Amylan CM1007 (Toray product, MFR: 21g / 10min), and Unitica Nylon A1020LP (Unitica product, MFR: 109g / 10min).

[0059] Specific examples of the above 66-nylon resin include Amylan CM3001N (Toray product, MFR: 103g / 10min).

[0060] Specific examples of the above polyester resins include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polycyclohexalenedimethylene terephthalate (PCT), polytrimethylene terephthalate (PTT), polyethylene naphthalate (PEN), liquid crystal polyester, etc.

[0061] Particularly suitable examples of thermoplastic resins (B) include Unitica Nylon A1020LP (6-nylon, manufactured by Unitica, MFR: 109 g / 10 min) and Amylan CM3001N (66-nylon, manufactured by Toray, MFR: 103 g / 10 min).

[0062] In addition, the average solubility parameter of the thermoplastic resin (B) after blending satisfies 10 to 15, and a thermoplastic resin with a solubility parameter of less than 10 can be suitably blended. Examples of thermoplastic resins with a solubility parameter of less than 10 include Prime PP J704UG (PP, solubility parameter 9.3) and Admer QF500 (maleic anhydride modified PP, solubility parameter 9.6).

[0063] From the perspective of more effectively increasing impact resistance, it is more desirable that the solubility parameter of each resin used in the thermoplastic resin (B) satisfies 10 to 15.

[0064] The average MFR of the thermoplastic resin (B) is preferably 10 g / min or more, and more preferably 20 g / min or more. By making the average MFR of the thermoplastic resin (B) 10 g / min or more, the melt viscosity when r-CF (A) and the thermoplastic resin (B) are mixed is reduced, and the breakdown of r-CF (A) can be suppressed, thereby enabling the expression of high mechanical properties. The upper limit of the average MFR of the thermoplastic resin (B) is not particularly limited, but from the perspective of ease of availability, it is typically 200 g / min or less.

[0065] 1-1b-1. Acid-modified thermoplastic elastomer (b-1)

[0066] The thermoplastic resin (B) may contain an acid-modified thermoplastic elastomer (b-1). Here, “thermoplastic elastomer” in this specification refers to a polymer that softens and becomes plastic when heated to a suitable temperature, exhibits elasticity when cooled, and does not exhibit a melting point by the DSC method. By combining r-CF (A) with the thermoplastic resin (B), and also including the acid-modified thermoplastic elastomer (b-1) as the thermoplastic resin (B), a thermoplastic resin composition with significantly improved compatibility and high impact resistance can be produced.

[0067] "Acid-modified thermoplastic elastomer" refers to a thermoplastic elastomer into which acid functional groups have been introduced through graft polymerization or the like. Preferred examples of acid-modified thermoplastic elastomers include acid-modified styrene-based elastomers and acid-modified olefin-based elastomers. Acid modification refers to introducing cyclic acid anhydride groups or carboxylic acid groups into the side chains of a copolymer, for example, using cyclic acid anhydrides such as succinic anhydride, maleic anhydride, glutaric anhydride, or phthalic anhydride.

[0068] Examples of the above-mentioned styrene-based elastomers include block copolymers composed of polystyrene blocks and elastomer blocks with a polyolefin structure. Specific examples include styrene-isoprene-styrene block copolymers (SIS), hydrogenated styrene / ethylene / propylene / styrene block copolymers (SEPS), styrene / butylene / styrene block copolymers (SBS), hydrogenated styrene / ethylene / butylene / styrene block copolymers (SEBS), styrene / butadiene / isoprene / styrene block copolymers (SBIS), and hydrogenated styrene / butadiene / isoprene / styrene block copolymers (SEEPS).

[0069] Examples of the above olefin-based elastomers include ethylene-propylene copolymer, ethylene-butene-1 copolymer, ethylene-hexene-1 copolymer, ethylene-octene-1 copolymer, ethylene-ethyl acrylate copolymer, ethylene-methacrylate copolymer, ethylene-propylene-diene terpolymer, isoprene rubber, nitrile rubber, polybutene rubber, etc.

[0070] Commercially available products include, for example, maleic anhydride modified isoprene rubber such as LIR-403 (product of Kuraray); modified isoprene rubber such as LIR-410 (product of Kuraray); carboxy-modified nitrile rubber such as Cranac 110, 221, 231 (product of Polyser); maleic anhydride modified polybutene such as Nisseki Polybutene (product of Shin Nippon Petroleum); ethylene methacrylic acid copolymer such as Nuquerel (product of Mitsui DuPont Polychemical); ethylene methacrylic acid copolymer such as Eucalon (product of Mitsubishi Chemical); and maleic anhydride modified ethylene-propylene rubber such as Tuffmer M (MA8510 (product of Mitsui Chemical)), TX-1215 (product of Mitsui Chemical); Maleic anhydride modified ethylene-butene rubber such as Toughmer M (MH7020 (product of Mitsui Chemical Co., Ltd.)); Maleic anhydride modified polyethylene such as HPR series (maleic anhydride modified EEA (product of Mitsui-DuPont Polychemicals)), Bondine (maleic anhydride modified EEA (product of Atopina)), Toughtec (maleic anhydride modified SEBS, M1943 (product of Asahi Kasei), Clayton (maleic anhydride modified SEBS, FG1901X (product of Clayton Polymer)), Toughfrene (maleic anhydride modified SBS, 912 (product of Asahi Kasei)), Septon (maleic anhydride modified SEPS (product of Kuraray)), Rexpearl (maleic anhydride modified EEA, ET-182G, 224M, 234M (product of Nippon Polyolefin)), and Aurorene (maleic anhydride modified EEA, 200S, 250S (product of Nippon Paper Chemical)). Examples include maleic anhydride modified polypropylene such as Admer (QB550, LF128 (product of Mitsui Chemical Co.)).

[0071] A particularly preferred example of an acid-modified thermoplastic elastomer (b-1) is a maleic anhydride-modified styrene-ethylene-butadiene-styrene copolymer. Commercially available acid-modified styrene-ethylene-butylene-styrene block copolymers include Asahi Kasei Chemicals’ Tufftac M1911: acid value 2 mg CH3ONa / g, MFR 4.5 g / 10 min, Asahi Kasei Chemicals’ Tufftac M1913: acid value 10 mg CH3ONa / g, MFR 5.0 g / 10 min, Asahi Kasei Chemicals’ Tufftac M1943: acid value 10 mg CH3ONa / g, MFR 8.0 g / 10 min, etc.

[0072] Since the acid-modified thermoplastic elastomer (b-1) can increase the impact strength of the resulting r-CFRP, it is preferable that the Charpy impact strength measured according to JIS K7111-1 be 20 kJ / m² or higher, and 30 kJ / m² or higher. It is more preferable. The upper limit of the Charpy impact strength of the acid-modified thermoplastic elastomer (b-1) is not specifically limited, and one that does not break can be suitably used.

[0073] The average MFR of the acid-modified thermoplastic elastomer (b-1) is preferably 1.0 g / 10 min or more, and more preferably 5.0 g / 10 min or more. Since the average MFR of the acid-modified thermoplastic elastomer (b-1) is within the above range, the melt viscosity during processing is reduced, which can suppress fiber breakage of r-CF (A) caused by processing and enable the expression of high physical properties.

[0074] The amount of acid-modified thermoplastic elastomer (b-1) in 100 mass% of the thermoplastic resin composition is preferably 5 to 20 mass% in order to further improve the compatibility of elastic modulus and impact strength, more preferably 5 to 15 mass%, and even more preferably 5 to 10 mass%.

[0075] The preferred acid value of the acid-modified thermoplastic elastomer (b-1) is 0.5 to 40 mg CH3ONa / g, and 1 to 30 mg CH3ONa / g is more preferred. By having the acid value of the acid-modified thermoplastic elastomer (b-1) in the range of 0.5 to 40 mg CH3ONa / g, the interfacial adhesion between r-CF (A) and the thermoplastic resin (B) can be improved. In addition, the acid value in this disclosure is a value measured according to JIS K-0070.

[0076] 1-1c. Arbitrary component

[0077] The present composition may contain inorganic fillers as optional components. Examples of inorganic fillers include silica, heat-dissipating fillers, talc, calcium silicate, wollastonite, montmorillonite, and hydrotalcite. Additionally, if necessary, other additives conventionally formulated for resin modification, such as weather stabilizers, light stabilizers, anti-aging agents, antioxidants, softeners, dispersants, fillers, colorants, lubricants, heat stabilizers, antistatic agents, UV absorbers, and flame retardants such as halogen-based, phosphorus-based, or metal oxides, may be added. Furthermore, metal soaps of alkali metals, alkaline earth metals, or zinc, nonionic surfactants, cationic surfactants, anionic surfactants, and amphoteric surfactants may be added.

[0078] 1-2. Method for manufacturing a thermoplastic resin composition

[0079] The present composition is obtained by kneading the components at the temperature at which the thermoplastic resin (B) melts. For example, r-CF (A), the thermoplastic resin (B), and, if necessary, various additives or coloring agents are added, and the mixture is kneaded using a batch mixer such as a kneader, roll mill, super mixer, high-speed mixer, ball mill, sand mill, attritor, or Banbury mixer, a single-screw extruder, a twin-screw extruder, or a rotary twin-screw mixer to form a resin composition in the form of pellets, powder, granules, or beads. Since the kneading force is strong and subsequent molding processing is easy, the method of forming it into pellets using a twin-screw extruder is suitable.

[0080] The present composition may be used as a masterbatch that is diluted with a molding resin during molding. Alternatively, a required amount of r-CF (A) may be mixed with a thermoplastic resin (B) to form a compound that is molded as is without diluting with a molding resin.

[0081] The amount of r-CF(A) in 100 mass% of the masterbatch is preferably 41 to 70 mass%, and more preferably 50 to 65 mass%. By setting the amount of r-CF(A) within the above range, the productivity and mechanical properties of the masterbatch can be improved. In the masterbatch, the resin used for dilution during molding may be the thermoplastic resin (B) exemplified above. Since it has excellent compatibility, it is preferable to use the same resin as the thermoplastic resin (B) used for the dispersion of r-CF(A). Because the present composition has excellent dispersibility of r-CF(A), it can be molded stably even when using a high-concentration resin composition such as the masterbatch.

[0082] When the present composition is used as a compound, the amount of r-CF(A) in 100 mass% of the compound is preferably 10 to 40 mass%, and more preferably 15 to 35 mass%. By setting the amount of r-CF(A) within the above range, the productivity and moldability of the compound can be achieved simultaneously.

[0083] 1-3. Molded body

[0084] A molded article according to the first embodiment is formed by molding from the present composition. The molding method is not particularly limited and can be manufactured by, for example, extrusion molding, injection molding, blow molding, etc. Since the present composition has excellent strength and excellent moldability, it is also suitable for molding injection-molded articles, such as automotive parts having complex shapes.

[0085] 2. Second embodiment

[0086] 2-1. Thermoplastic resin composition

[0087] The thermoplastic resin composition of the second embodiment (hereinafter also referred to as the composition in the second embodiment) is a thermoplastic resin composition for carbon fiber reinforcement containing recycled carbon fiber (A) and a thermoplastic resin (B), wherein the oxygen content in the recycled carbon fiber (A) is 5.0 mass% or more. The thermoplastic resin (B) has an average solubility parameter of 9 to 15 and also includes at least one of an acrylic resin (ii-B1) and a styrene resin (ii-B2), and the glass transition temperature of the acrylic resin (ii-B1) and the styrene resin (ii-B2) is 0°C or higher.

[0088] As a result of repeated diligent examinations by the inventors, it was found that by combining r-CF (A) having an oxygen content of 5.0 mass% or more and a thermoplastic resin (B) having an average solubility parameter of 9 to 15, and including at least one of an acrylic resin (ii-B1) and a styrene resin (ii-B2), and having a glass transition temperature of the acrylic resin (ii-B1) and the styrene resin (ii-B2) of 0°C or higher, the compatibility between the resin and the recycled carbon fiber can be significantly improved, and the adhesion between the resin and the recycled carbon fiber can be improved.

[0089] According to the present composition, impact strength, productivity, and elastic modulus are improved. Furthermore, due to the excellent compatibility between the resin and the recycled carbon fiber, deposits on the die of the manufacturing equipment can be suppressed. By suppressing deposits, problems such as deposits being mixed into the product or deposits clogging the die holes and causing material ejection failures can be prevented, thereby increasing productivity. Additionally, as the adhesion between the thermoplastic resin (B) and r-CF (A) increases, the elastic modulus can be increased. As a result, it is expected that parts that have previously used metal materials can be replaced with r-CFRP, which has excellent lightweight properties. That is, even when using recycled carbon fiber, a thermoplastic resin composition and a molded article containing recycled carbon fiber with excellent productivity and impact resistance can be provided. Each component will be described in detail below.

[0090] 2-1a. Regenerated carbon fiber (A)

[0091] The r-CF (regenerated carbon fiber) of the second embodiment is omitted by referring to the description of the r-CF of 1-1a above.

[0092] By combining a thermoplastic resin (B) of the second embodiment, which has a solubility parameter of 9 to 15 and also includes at least one of an acrylic resin and a styrene resin, and has a glass transition temperature of 0°C or higher for the acrylic resin (ii-B1) and the styrene resin (ii-B2), the compatibility between them can be significantly increased. Similarly, by lowering the diffraction intensity of the (002) plane of r-CF (A), the adhesion with the thermoplastic resin (B) of the second embodiment can be improved.

[0093] 2-1b. Thermoplastic resin (B)

[0094] The thermoplastic resin (B) according to the second embodiment has an average solubility parameter of 9 to 15. In addition, the thermoplastic resin (B) may be used in combination of one or two or more types, and includes at least one of an acrylic resin (ii-B1) having a glass transition temperature of 0°C or higher and a styrene resin (ii-B2) having a glass transition temperature of 0°C or higher.

[0095] When using two or more types of thermoplastic resins, the solubility parameter of each thermoplastic resin does not need to be in the range of 9 to 15, but the average solubility parameter when blending the thermoplastic resins used needs to be in the range of 9 to 15.

[0096] By combining a thermoplastic resin (B) comprising at least one of an acrylic resin (ii-B1) and a styrene resin (ii-B2) having an average solubility parameter of 9 to 15 and a glass transition temperature of 0°C or higher, with r-CF (A) having an oxygen content of 5.0 mass% or higher, as described above, the compatibility between r-CF (A) and the thermoplastic resin (B) can be significantly increased to improve adhesion. As a result, impact resistance can be improved. A more preferred range for the solubility parameter of the thermoplastic resin (B) is 9 to 12.

[0097] From the perspective of more effectively increasing impact resistance, it is more desirable that the solubility parameter of each resin used in the thermoplastic resin (B) satisfies 9 to 15.

[0098] The thermoplastic resin (B) may be used in combination with a resin other than an acrylic resin (ii-B1) or a styrene resin (ii-B2) having a solubility parameter of 9 to 15, provided that it does not interfere with the effects of the second embodiment, but it is preferable that at least one of the acrylic resin (ii-B1) and the styrene resin (ii-B2) is the main component. If the average solubility parameter is within this range, other thermoplastic resins such as acrylic resins other than acrylic resin (ii-B1) and styrene resin (ii-B2), or styrene resins, may be used in combination.

[0099] The main component refers to the thermoplastic resin that has the highest content among the components constituting the thermoplastic resin (B).

[0100] Even when using recycled carbon fiber (A), from the perspective of being able to produce a thermoplastic resin composition with excellent productivity and impact resistance, the content of acrylic resin (ii-B1) or styrene resin (ii-B2) in 100 mass% of thermoplastic resin (B) is preferably 52 to 95 mass%, more preferably 55 to 100 mass%, and even more preferably 60 to 90 mass%. In addition, the above content is the total content when both acrylic resin (ii-B1) and styrene resin (ii-B2) are included.

[0101] The acrylic resin (ii-B1) and the styrene resin (ii-B2) have a glass transition temperature of 0°C or higher, preferably 0°C or higher and 140°C or lower, and more preferably 25°C to 130°C.

[0102] Thus, high productivity and mechanical properties can be satisfied.

[0103] The glass transition temperature in this specification is a value obtainable using differential scanning calorimetry (DSC) in accordance with JIS K7121:2012.

[0104] The solubility parameters of the acrylic resin (ii-B1) and styrene resin (ii-B2) contained in the thermoplastic resin (B) are preferably 9 to 15 in terms of high productivity and mechanical properties, and more preferably 9 to 12.

[0105] The average MFR of the thermoplastic resin (B) is preferably 10 g / min or more, and more preferably 20 g / min or more. By making the average MFR of the thermoplastic resin (B) 10 g / min or more, the melt viscosity when r-CF (A) and the thermoplastic resin (B) are mixed is reduced, and the breakdown of r-CF (A) can be suppressed, thereby enabling the expression of high mechanical properties. The upper limit of the average MFR of the thermoplastic resin (B) is not particularly limited, but from the perspective of ease of availability, it is typically 200 g / min or less.

[0106] [Acrylic resin (ii-B1)]

[0107] The acrylic resin (ii-B1) is an acrylic resin having a glass transition temperature of 0°C or higher, and can be obtained by polymerizing a (meth)acrylic monomer. Examples of monomers include (meth)acrylic monomers having alkyl groups, (meth)acrylic monomers having hydroxyl groups, (meth)acrylic monomers having carboxyl groups, (meth)acrylic monomers having glycidyl groups, and acrylic monomers having vinyl ester groups such as vinyl acetate or vinyl propionate. Among these, polymethyl methacrylate (PMMA) resin, which is a polymer of methyl methacrylate, is preferred because it can achieve a high elastic modulus.

[0108] Specific examples of acrylic resins (ii-B1) include acrylic PET TF-9 (product of Mitsubishi Chemical, solubility parameter: 9.2, MFR 20g / 10 min).

[0109] [Styrene-based resin (ii-B2)]

[0110] Styrene-based resins (ii-B2) are styrene-based resins having a glass transition temperature of 0°C or higher, and are resins having styrene-based monomers as monomers. In addition to homopolymers of styrene-based monomers, styrene-based resins obtained by copolymerizing other vinyl monomers or rubbery polymers that can be copolymerized with them as needed may be examples.

[0111] Examples of styrene-based monomers include styrene derivatives such as styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, vinylxylene, ethylstyrene, dimethylstyrene, p-tert-butylstyrene, vinylnaphthalene, methoxystyrene, monobromstyrene, dibromstyrene, fluorostyrene, and tribromstyrene, and styrene is particularly preferred from the perspective of excellent moldability.

[0112] Other vinyl monomers copolymerizable with styrene-based monomers include vinyl cyanide compounds such as acrylonitrile and methacrylonitrile; aryl esters of acrylic acid such as phenyl acrylate and benzyl acrylate; alkyl esters of acrylic acid such as methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, amyl acrylate, hexyl acrylate, 2-ethylhexyl acrylate, octyl acrylate, cyclohexyl acrylate, and dodecyl acrylate; aryl esters of methacrylate such as phenyl methacrylate and benzyl methacrylate; methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, amyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, and octyl methacrylate. Examples include alkyl methacrylate esters such as cyclohexyl methacrylate and dodecyl methacrylate, epoxy group-containing methacrylic acid esters such as glycidyl methacrylate, maleimide monomers such as maleimide, N-methylmaleimide, and N-phenylmaleimide, α,β-unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, phthalic acid, and itaconic acid, and their anhydrides.

[0113] As rubbery polymers copolymerizable with styrene-based monomers, these include polybutadiene, polyisoprene, random copolymers and block copolymers of styrene / butadiene, acrylonitrile / butadiene copolymers, copolymers of butadiene and alkyl acrylate or alkyl methacrylate esters, diene copolymers such as butadiene / isoprene copolymers, copolymers of ethylene and α-olefins such as ethylene / propylene random copolymers and block copolymers, random copolymers and block copolymers of ethylene / butene, copolymers of ethylene and unsaturated carboxylic acid esters such as ethylene / methyl methacrylate copolymers and ethylene / butyl acrylate copolymers, copolymers of ethylene and aliphatic vinyls such as ethylene / vinyl acetate copolymers, and non-conjugated diene polymers of ethylene and propylene such as ethylene / propylene / hexadiene copolymers. Examples include acrylic rubbers such as polyacrylate butyl, and composite rubbers having a structure in which polyorganosiloxane rubber components and polyalkyl (meth)acrylate rubber components are intertwined so that they cannot be separated.

[0114] Examples of styrene-based resins composed of such monomers include polystyrene, styrene / butadiene / styrene copolymer (SBS), impact-resistant polystyrene (HIPS), acrylonitrile / styrene copolymer (AS resin), acrylonitrile / butadiene / styrene copolymer (ABS resin), methyl methacrylate / butadiene / styrene copolymer (MBS resin), methyl methacrylate / acrylonitrile / butadiene / styrene copolymer (MABS resin), acrylonitrile / acrylic rubber / styrene copolymer (AAS resin), acrylonitrile / ethylene propylene rubber / styrene copolymer (AES resin), and styrene / IPN type rubber copolymer, or mixtures thereof.

[0115] In addition, as a rubbery polymer copolymerizable with styrene-based monomers, a polymer composed of polybutadiene or polyisoprene, in which the unsaturated bonds are hydrogenated (hydrogenated) may be cited. Specific examples of such cases include hydrogenated styrene / butadiene / styrene copolymer (hydrogenated SBS) and hydrogenated styrene / isoprene / styrene copolymer (SEPS).

[0116] Among these, acrylonitrile / styrene copolymer (AS resin) or acrylonitrile / butadiene / styrene copolymer (ABS resin) is preferred because of its good compatibility with r-CF(A), and acrylonitrile / butadiene / styrene copolymer (ABS resin) is more preferred because of its good impact resistance.

[0117] Specific examples of AS resin include Sebian 090SF (product of Daicel Miraise, solubility parameter MFR 23g / 10 min). Specific examples of ABS resin include Sebian T-500SF (product of Daicel Miraise, MFR 25g / 10 min).

[0118] 2-1b-1. Acid-modified thermoplastic elastomer (b-1)

[0119] The thermoplastic resin (B) of the present composition may contain an acid-modified thermoplastic elastomer (b-1). The acid-modified thermoplastic elastomer (b-1) of the second embodiment is omitted by referring to the description of the acid-modified thermoplastic elastomer (b-1) of 1-1b-1, except for the details described below.

[0120] In the second embodiment, when using an acid-modified thermoplastic elastomer (b-1), since elastic modulus and impact strength can be achieved, the content of the acid-modified thermoplastic elastomer (b-1) in 100 mass% of the thermoplastic resin (B) is preferably 3 to 40 mass%, more preferably 5 to 35 mass%, and even more preferably 7 to 30 mass%.

[0121] In addition, it is preferable that the glass transition temperature of the acid-modified thermoplastic elastomer (b-1) be less than 0°C.

[0122] 2-1c. Arbitrary component

[0123] Any component of the present composition is omitted by referring to the description of any component in 1-1c above.

[0124] 2-2. Method for manufacturing a thermoplastic resin composition

[0125] The method for manufacturing the present composition is omitted by utilizing the description of the method for manufacturing the thermoplastic resin composition of 1-2 above.

[0126] 2-3. Molded body

[0127] The description of the molded body according to the second embodiment is omitted by referring to the description of the molded body of 1-3 above.

[0128] 3. Third embodiment

[0129] 3-1. Thermoplastic resin composition

[0130] The thermoplastic resin composition of the third embodiment (hereinafter also referred to as the composition in the third embodiment) is a thermoplastic resin composition for carbon fiber reinforcement containing recycled carbon fiber (A) and a thermoplastic resin (B). The oxygen content in the recycled carbon fiber (A) is 5.0 mass% or more, and the acid value of the recycled carbon fiber (A) is 0.002 to 0.080 mmol / g. In addition, the thermoplastic resin (B) has an average flow onset temperature of 250°C or less and also includes at least one of a polyester resin (iii-B1) and a polycarbonate resin (iii-B2).

[0131] As a result of repeated diligent examinations by the inventors, it was found that by combining r-CF (A), in which the oxygen content in the recycled carbon fiber (A) is 5.0 mass% or more and the acid value is 0.002 to 0.080 mmol / g; and a thermoplastic resin (B), which has an average flow initiation temperature of 250°C or less and includes at least one of a polyester resin (iii-B1) and a polycarbonate resin (iii-B2), the compatibility between the resin and the recycled carbon fiber can be significantly improved, and the adhesion between the resin and the recycled carbon fiber can be improved.

[0132] According to the thermoplastic resin composition of the present embodiment, impact strength, productivity, and elastic modulus are improved. In addition, due to the excellent compatibility between the resin and the recycled carbon fiber, deposits on the die of the manufacturing equipment can be suppressed. By suppressing deposits, problems such as deposits being mixed into the product or deposits clogging the die holes and causing material ejection failures can be suppressed, thereby increasing productivity. Furthermore, as the adhesion between the thermoplastic resin (B) and r-CF (A) increases, the elastic modulus can be increased. As a result, it is expected that parts that have previously used metal materials can be replaced with r-CFRP, which has excellent lightweight properties. Each component will be described in detail below.

[0133] 3-1a. Recycled carbon fiber (A)

[0134] The r-CF (regenerated carbon fiber) of the third embodiment has an oxygen content of 5.0 mass% or more in the r-CF (A) and an acid value of 0.002 to 0.080 mmol / g. By combining a thermoplastic resin (B) which has an average flow onset temperature of 250°C or less and includes at least one of a polyester resin (iii-B1) and a polycarbonate resin (iii-B2) as described below, and r-CF (A) which has an oxygen content of 5.0 mass% or more and an acid value of 0.002 to 0.080 mmol / g, the compatibility between them can be significantly increased.

[0135] It is preferable that the upper limit of the acid value of r-CF(A) be 0.080 mmol / g or less in order to maintain good strength of the thermoplastic resin composition. A more preferable range is 0.005 to 0.060 mmol / g.

[0136] The r-CF (regenerated carbon fiber) of the third embodiment is omitted by referring to the description of the r-CF of 1-1a above, except for the matters described above.

[0137] 3-1b. Thermoplastic resin (B)

[0138] The thermoplastic resin (B) according to the third embodiment has an average flow start temperature of 250°C or less. In addition, the thermoplastic resin (B) may be used in combination of one or more types, and includes at least one of a polyester resin (iii-B1) and a polycarbonate resin (iii-B2).

[0139] When using two or more types, the flow start temperature of each thermoplastic resin does not need to be in the range of 250°C or lower, and the average flow start temperature when blending the thermoplastic resins used needs to be in the range of 250°C or lower.

[0140] Here, the flow initiation temperature refers to the temperature at which the melt viscosity of a thermoplastic resin becomes 4800 Pa·s or less when passed through a capillary tube with a die hole diameter of φ1 mm and a die length of 1 mm under a pressure of 9.8 MPa in the evaluation of melt viscosity by a flow tester.

[0141] The lower limit of the average flow start temperature of the thermoplastic resin (B) is not particularly limited. A more preferred range is 220 to 240°C. By combining a thermoplastic resin (B) having an average flow start temperature of 250°C or less and comprising at least one of a polyester resin (iii-B1) and a polycarbonate resin (iii-B2); and r-CF (A) of the third embodiment, high productivity and mechanical properties can be obtained.

[0142] When there are two or more types of thermoplastic resins (B), the average flow start temperature of the thermoplastic resins (B) after blending must satisfy 250°C or less, and from the perspective of more effectively improving mechanical properties, it is more desirable that the flow start temperature of each resin used in the thermoplastic resins (B) satisfy 250°C or less.

[0143] Since the thermoplastic resin (B) can increase the impact strength of the resulting r-CFRP, it is preferable that the Charpy impact strength measured according to JIS K7111-1 be 3 kJ / m² or higher, and 5 kJ / m² 2 It is more desirable to have the above. The upper limit of the Charpy impact strength of the thermoplastic resin (B) is not particularly limited, and one that does not break can be suitably used.

[0144] In terms of fluidity, the content of polyester resin (iii-B1) or polycarbonate resin (iii-B2) in the thermoplastic resin (B) is preferably 50 to 100 mass% of 100 mass% of the thermoplastic resin (B), more preferably 52 to 95 mass%, and even more preferably 60 to 90 mass%. Additionally, the above content is the total content when both polyester resin (iii-B1) and polycarbonate resin (iii-B2) are included.

[0145] The flow initiation temperature of the polyester resin (iii-B1) or polycarbonate resin (iii-B2) contained in the thermoplastic resin (B) is preferably 250°C or lower for the sake of high productivity and mechanical properties, and more preferably 220 to 240°C.

[0146] As a suitable polyester resin (iii-B1), for example, a thermoplastic resin composed of a saturated dicarboxylic acid and a saturated dihydric alcohol can be used.

[0147] As saturated dicarboxylic acids, aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, naphthalene-1,4- or 2,6-dicarboxylic acid, diphenyl ether-4,4'-dicarboxylic acid, diphenyldicarboxylic acids, and diphenoxyethanediethanedicarboxylic acids, aliphatic dicarboxylic acids such as adipic acid, sebacic acid, azelaic acid, and decane-1,10-dicarboxylic acid, and alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid may be used.

[0148] As saturated dihydric alcohols, aliphatic glycols such as ethylene glycol, propylene glycol, trimethylene glycol, tetramethylene glycol, diethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, hexamethylene glycol, dodecamethylene glycol, and neopentyl glycol, cyclohexanedimethanol, 2,2-bis(4'-β-hydroxyethoxyphenyl)propane, and other aromatic diols may be used.

[0149] Specific examples of preferred polyester resins (iii-B1) include PET-G, I-PET, polybutylene terephthalate (PBT), polycyclohexalenedimethylene terephthalate (PCT), polytrimethylene terephthalate (PTT), etc.

[0150] As for the polycarbonate resin (iii-B2), for example, a resin that is easily produced by reacting an aromatic dihydroxy compound with a carbonate precursor such as phosgene or a carbonate diester can be used. The resin can be produced by known reactions, for example, by an interfacial method when using phosgene, or by an ester exchange method in which the reaction is carried out in a molten form when using a carbonate diester.

[0151] Aromatic dihydroxy compounds include, for example, 2,2-bis(4-hydroxyphenyl)propane (Bisphenol A), bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, bis(4-hydroxyphenyl)phenylmethane, 2,2-bis(4-hydroxy-3-methyl)phenyl)propane, 1,1-bis(4-hydroxy-3-t-butylphenyl)propane, 2,2-bis(4-hydroxy-3-bromophenyl)propane, 2,2-bis(4-hydroxy-3,5-dibromophenyl)propane, 2,2-bis(4-hydroxy-3,5-dichlorophenyl)propane, etc. Bis(hydroxyaryl)alkanes, bis(hydroxyaryl)cycloalkanes such as 1,1-bis(4-hydroxyphenyl)cyclopentane, 1,1-bis(4-hydroxyphenyl)cyclohexane, dihydroxydiaryl ethers such as 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyldiphenyl ether, dihydroxydiaryl sulfides such as 4,4'-dihydroxydiphenyl sulfide, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide, dihydroxydiaryl sulfides such as 4,4'-dihydroxydiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide, 4,4'-dihydroxydiphenylsulfone, Examples include dihydroxydiarylsulfones such as 4,4'-dihydroxy-3,3'-dimethyldiphenylsulfone. These are used alone or in a mixture of two or more. In addition to these, piperazine, dipiperidylhydroquinone, resorcin, and 4,4'-dihydroxydiphenyls may also be used in combination. Furthermore, branched aromatic polycarbonate resins may be used in combination with polyfunctional compounds such as phloroglucin.

[0152] Examples of carbonate precursors that react with aromatic dihydroxy compounds include diaryl carbonates such as phosgene, diphenyl carbonate, and ditolyl carbonate, and dialkyl carbonates such as dimethyl carbonate and diethyl carbonate.

[0153] The average MFR of the thermoplastic resin (B) is preferably 10 g / min or more, and more preferably 20 g / min or more. By making the average MFR of the thermoplastic resin (B) 10 g / min or more, the melt viscosity when r-CF (A) and the thermoplastic resin (B) are mixed is reduced, and the breakdown of r-CF (A) can be suppressed, thereby enabling the expression of high mechanical properties. The upper limit of the average MFR of the thermoplastic resin (B) is not particularly limited, but from the perspective of ease of availability, it is typically 200 g / min or less.

[0154] 3-1b-1. Acid-modified thermoplastic elastomer (b-1)

[0155] The thermoplastic resin (B) of the present composition may contain an acid-modified thermoplastic elastomer (b-1). The acid-modified thermoplastic elastomer (b-1) of the third embodiment is omitted by referring to the description of the acid-modified thermoplastic elastomer (b-1) of 1-1b-1 above.

[0156] 3-1c. Arbitrary component

[0157] Any component of the present composition is omitted by referring to the description of any component in 1-1c above.

[0158] 3-2. Method for manufacturing a thermoplastic resin composition

[0159] The method for manufacturing the present composition is omitted by utilizing the description of the method for manufacturing the thermoplastic resin composition of 1-2 above.

[0160] 3-3. Molded body

[0161] The description of the molded body according to the third embodiment is omitted by referring to the description of the molded body of 1-3 above.

[0162] 4. Fourth embodiment

[0163] 4-1. Thermoplastic resin composition

[0164] The thermoplastic resin composition of the fourth embodiment (hereinafter also referred to as the composition in the fourth embodiment) is a thermoplastic resin composition for carbon fiber reinforcement containing recycled carbon fiber (A) and a thermoplastic resin (B). The oxygen content in the recycled carbon fiber (A) is 5.0 mass% or more. The thermoplastic resin (B) comprises a polyolefin resin having a melting point of 100°C or higher (except in the case of an acid-modified thermoplastic resin) (iv-B), and at least one of acid-modified polypropylene (iv-b-1) and a thermoplastic elastomer (iv-b-2). The acid-modified polypropylene (iv-b-1) has a melting point of 130°C or higher.

[0165] As a result of repeated diligent examinations by the inventors, it was found that by combining r-CF (A) having an oxygen content of 5.0 mass% or more, a polyolefin resin having a melting point of 100°C or higher (except in cases where it is an acid-modified thermoplastic resin) (iv-B) (hereinafter also simply referred to as polyolefin resin (iv-B)); and a thermoplastic resin (B) comprising at least one of acid-modified polypropylene (iv-b-1) and a thermoplastic elastomer (iv-b-2), the compatibility between the polyolefin resin and the recycled carbon fiber is significantly improved, and the adhesion between the polyolefin resin and the recycled carbon fiber can be improved. According to the present composition, tensile strength, elastic modulus, impact strength, load bending temperature, and productivity are improved. In addition, due to the excellent compatibility between the resin and the recycled carbon fiber, deposits on the die of the manufacturing equipment can be suppressed. By suppressing sedimentation, problems such as sediment being mixed into the product or sediment clogging the die holes and causing material ejection failures can be suppressed, thereby increasing productivity. In addition, as the adhesion between the thermoplastic resin (B) and r-CF (A) is enhanced, tensile strength, elastic modulus, impact strength, and load bending temperature can be increased. As a result, it is expected that parts that have previously used metal materials can be replaced with r-CFRP, which has excellent lightweight properties. Each component will be described in detail below.

[0166] 4-1a. Regenerated carbon fiber (A)

[0167] The r-CF (regenerated carbon fiber) of the fourth embodiment is omitted by referring to the description of the r-CF of 1-1a above.

[0168] 4-1b. Thermoplastic resin (B)

[0169] The thermoplastic resin (B) according to the fourth embodiment comprises at least one of a polyolefin resin (iv-B), an acid-modified polypropylene (iv-b-1), and a thermoplastic elastomer (iv-b-2). The acid-modified polypropylene (iv-b-1) has a melting point of 130°C or higher.

[0170] Among these, it is preferable to include acid-modified polypropylene (iv-b-1) and thermoplastic elastomer (iv-b-2) so as to increase adhesion with r-CF(A).

[0171] "Acid-modified thermoplastic resin" refers to a thermoplastic resin into which acidic functional groups have been introduced through graft polymerization or the like.

[0172] In addition, to the extent that it does not interfere with the effects of the present invention, a thermoplastic resin other than a polyolefin resin (iv-B), acid-modified polypropylene (iv-b-1), and thermoplastic elastomer (iv-b-2) may be used, but it is preferable that the main component be a polyolefin resin having a melting point of 100°C or higher (except in the case of an acid-modified thermoplastic resin).

[0173] The main component refers to the thermoplastic resin that has the highest content among the components constituting the thermoplastic resin (B).

[0174] The melting point of the polyolefin resin (iv-B), which has a melting point of 100°C or higher, is preferably 100 to 180°C, and more preferably 105 to 170°C. Since the melting point is within the above range, compatibility with the acid-modified polypropylene (iv-b-1) or thermoplastic elastomer (iv-b-2) described later is improved, and because the dispersibility of the acid-modified polypropylene (iv-b-1) and thermoplastic elastomer (iv-b-2) in the polyolefin resin is improved, the adhesion between the thermoplastic resin (B) and r-CF (A) is excellent.

[0175] The melting point in this specification is a value measured by the differential scanning calorimetry (DSC) method (a value obtained by a Seiko Instruments product, differential scanning calorimetry DSC6200, at a heating rate of 10℃ / min).

[0176] Since the content of the polyolefin resin (iv-B) having a melting point of 100°C or higher in the thermoplastic resin (B) can increase strength and elastic modulus, it is preferable that the content be 50 to 99 mass% of the thermoplastic resin (B) in 100 mass%, more preferable that it be 52 to 98 mass%, and even more preferable that it be 55 to 97 mass%.

[0177] [Polyolefin resin (iv-B)]

[0178] Examples of polyolefin resins (iv-B) include homopolymers of α-olefins with 2 to 8 carbon atoms, such as ethylene, propylene, and 1-butene, or (co)polymers of these α-olefins with other α-olefins with 2 to 18 carbon atoms, such as ethylene, propylene, 1-butene, 3-methyl-1-butene, 1-pentene, 4-methyl-1-pentene, 4,4-dimethyl-1-pentene, 1-hexene, 4-methyl-1-hexene, 1-heptene, 1-octene, 1-decene, and 1-octadecene.

[0179] The polyolefin resin (iv-B) is not limited to a melting point of 100°C or higher.

[0180] Specifically, examples include ethylene homopolymers such as linear low-density polyethylene (LLDPE), low-density polyethylene (LDPE), and high-density polyethylene (HDPE); ethylene copolymers such as ethylene-propylene copolymer, ethylene-1-butene copolymer, ethylene-propylene-1-butene copolymer, ethylene-4-methyl-1-pentene copolymer, ethylene-1-hexene copolymer, ethylene-1-heptene copolymer, and ethylene-1-octene copolymer; propylene homopolymer (homo PP), propylene-ethylene block copolymer (block PP), propylene-ethylene random copolymer (random PP), propylene-ethylene-1-butene copolymer, propylene-ethylene-4-methyl-1-pentene copolymer, and propylene-ethylene-1-hexene copolymer; and propylene copolymers such as propylene-ethylene-1-hexene copolymer. These polyolefin resins may be used as a single type or in combination of two or more types. Propylene-based resins are preferred because they can achieve high mechanical properties, and among them, propylene homopolymers (homo PP) are even more preferred because they can increase the load bending temperature.

[0181] In this specification, the melt flow rate (MFR) of the thermoplastic resin (B) is preferably 0.1 to 100 g / 10 min, more preferably 10 to 80 g / 10 min, and more preferably 20 to 60 g / 10 min. By having the MFR of the thermoplastic resin (B) within the above range, the destruction of r-CF (A) does not occur during mixing, and high physical properties can be exhibited. In addition, the MFR in the present invention is a value measured according to JIS K-7210-1:2014.

[0182] Specific examples of thermoplastic resins include Prime Polypro J229E (random PP, MFR 50g / 10 min, Prime Polymer Co. product), Prime Polypro J708UG (block PP, MFR 45g / 10 min), and Sunallomer PM900A (Sunallomer Co. product, homo PP, MFR 30g / 10 min).

[0183] [Acid-modified polypropylene (iv-b-1)]

[0184] By using acid-modified polypropylene (iv-b-1), the adhesion between r-CF (A) and the thermoplastic resin (B) is improved. Acid-modified polypropylene (iv-b-1) is acid-modified polypropylene with a melting point of 130°C or higher in the DSC method, and refers to a propylene-based resin into which acidic functional groups are introduced by graft polymerization or the like. Examples of acidic functional groups include cyclic acid anhydrides such as succinic anhydride, maleic anhydride, glutaric anhydride, and phthalic anhydride. The preferred melting point of acid-modified polypropylene (iv-b-1) is 130 to 200°C, and 135 to 180°C is more preferred. By using acid-modified polypropylene with a melting point in the above range, the difference in melting point with other components of the thermoplastic resin (B) is reduced, and the dispersibility of acid-modified polypropylene (iv-b-1) within the thermoplastic resin (B) is improved. Therefore, the adhesion between the thermoplastic resin (B) and r-CF (A) is improved.

[0185] The melting point in this specification is a value measured by the differential scanning calorimetry (DSC) method (a value obtained by a differential scanning calorimeter DSC6200 of Seiko Instruments at a heating rate of 10℃ / min).

[0186] The acid-modified polypropylene (iv-b-1) in the fourth embodiment is at 220°C and a shear rate of 1.2 × 10⁻⁶ 3 sec -1 The melting viscosity (ηc) of which is 1 to 500 Pa·s It is preferable that the melt viscosity be 10 to 500 Pa·s, more preferable that it be 20 to 400 Pa·s, and particularly preferable that it be 50 to 300 Pa·s. Since the melt viscosity at 220°C is within the above range, the difference in melt viscosity with the thermoplastic resin (B) during mixing is reduced, and the dispersibility of the acid-modified polypropylene (iv-b-1) is improved, thereby improving the interfacial adhesion between r-CF (A) and the thermoplastic resin (B). In addition, the elastic modulus and load bending temperature are improved, and even when recycled carbon fibers are used, it is possible to make a molded article containing recycled carbon fibers that has excellent productivity and excellent impact resistance.

[0187] In this specification, the melt viscosity is defined according to JIS K7199:1999 at a shear rate of 1.2×10 at 220°C. 3 sec -1 This is the value when measured.

[0188] The acid value of the acid-modified polypropylene (iv-b-1) resin is preferably 0.1 to 100 mgKOH / g, and more preferably 1 to 50 mgKOH / g. By having the acid value of the acid-modified polypropylene (iv-b-1) within the above range, the interfacial adhesion between r-CF (A) and the thermoplastic resin (B) can be improved without causing aggregation of r-CF (A).

[0189] In addition, the acid value in this specification is a value measured according to JIS K-0070.

[0190] In terms of achieving compatibility between tensile strength and load bending temperature, the amount of acid-modified polypropylene (iv-b-1) is preferably 1 to 40 mass% of the thermoplastic resin composition, more preferably 1 to 30 mass%, and even more preferably 5 to 20 mass%.

[0191] If the amount of acid-modified polypropylene (iv-b-1) is within this range, the interfacial adhesion between r-CF (A) and the thermoplastic resin (B) can be improved, and the occurrence of deposits at the die tip can be further suppressed.

[0192] The amount of acid-modified polypropylene (iv-b-1) blended is preferably 3 to 80 parts by mass per 100 parts by mass of polyolefin resin, more preferably 5 to 75 parts by mass, and particularly preferably 10 to 40 parts by mass. By having the amount of acid-modified polypropylene (iv-b-1) blended with polyolefin resin (iv-B) within the above range, strength and load bending temperature can be achieved.

[0193] Specific examples of acid-modified polypropylene (iv-b-1) include Admer QB550 (product of Mitsui Chemical, melt viscosity 200 MPa·s, acid value 2.3 mgKOH / g) and Modic P-908 (product of Mitsubishi Chemical, melt viscosity 150 MPa·s, acid value 12.8 mgKOH / g).

[0194] The acid value of acid-modified polypropylene (iv-b-1) can be determined by measuring it according to JIS K-0070.

[0195] [Thermoplastic elastomer (iv-b-2)]

[0196] The thermoplastic elastomer (iv-b-2) is formulated to improve the adhesion between r-CF (A) and the thermoplastic resin (B). The thermoplastic elastomer (iv-b-2) can be classified into acid-modified thermoplastic elastomers (iv-b-2x) and non-acid-modified thermoplastic elastomers (iv-b-2y).

[0197] To further enhance adhesion with r-CF(A), it is preferable to use an acid-modified thermoplastic elastomer (iv-b-2x).

[0198] In this specification, “thermoplastic elastomer” refers to a polymer that softens and becomes plastic when heated to a suitable temperature, exhibits elasticity when cooled, and does not exhibit a melting point by the DSC method. By including r-CF (A), a polyolefin resin as a thermoplastic resin (B), and a thermoplastic elastomer (iv-b-2), a thermoplastic resin composition with significantly improved compatibility and high impact resistance can be prepared.

[0199] "Acid-modified thermoplastic elastomer" refers to a thermoplastic elastomer into which acid functional groups have been introduced through graft polymerization or the like. Preferred examples of acid-modified thermoplastic elastomers include acid-modified styrene-based elastomers and acid-modified olefin-based elastomers. Acid modification refers to introducing cyclic acid anhydride groups or carboxylic acid groups into the side chains of a copolymer, for example, using cyclic acid anhydrides such as succinic anhydride, maleic anhydride, glutaric anhydride, or phthalic anhydride.

[0200] The preferred acid value of the acid-modified thermoplastic elastomer (iv-b-2x) is 0.5 to 40 mgCH3ONa / g, and 1 to 30 mgCH3ONa / g is more preferred. By having the acid value of the acid-modified thermoplastic elastomer (iv-b-2x) in the range of 0.5 to 40 mgCH3ONa / g, the interfacial adhesion between r-CF (A) and the thermoplastic resin (B) can be improved.

[0201] Examples of the above-mentioned styrene-based elastomers include block copolymers composed of polystyrene blocks and elastomer blocks with a polyolefin structure. Specific examples include styrene-isoprene-styrene block copolymer (SIS), hydrogenated styrene / ethylene / propylene / styrene block copolymer (SEPS), styrene / butylene / styrene block copolymer (SBS), hydrogenated styrene / ethylene / butylene / styrene block copolymer (SEBS), styrene / butadiene / isoprene / styrene block copolymer (SBIS), and hydrogenated styrene / butadiene / isoprene / styrene block copolymer (SEEPS).

[0202] Examples of the above olefin-based elastomers include ethylene-propylene copolymer, ethylene-butene-1 copolymer, ethylene-hexene-1 copolymer, ethylene-octene-1 copolymer, ethylene-ethyl acrylate copolymer, ethylene-methacrylate copolymer, ethylene-propylene-diene terpolymer, isoprene rubber, nitrile rubber, polybutene rubber, etc.

[0203] Commercially available acid-modified thermoplastic elastomers (iv-b-2x) include, for example, maleic anhydride modified isoprene rubber such as LIR-403 (manufactured by Kuraray); modified isoprene rubber such as LIR-410 (manufactured by Kuraray); carboxyl-modified nitrile rubber such as Cranac 110, 221, 231 (manufactured by Polyser); maleic anhydride modified polybutene such as Nisseki Polybutene (manufactured by Shin Nippon Petroleum); ethylene methacrylic acid copolymer such as Nuquerel (manufactured by Mitsui DuPont Polychemical); ethylene methacrylic acid copolymer such as Eucalon (manufactured by Mitsubishi Chemical); and maleic anhydride modified ethylene-propylene rubber such as Tuffmer M (MA8510 (manufactured by Mitsui Chemical)), TX-1215 (manufactured by Mitsui Chemical); Maleic anhydride modified ethylene-butene rubber such as Toughmer M (MH7020 (product of Mitsui Chemical Co., Ltd.)); Examples include maleic anhydride modified polyethylenes such as the HPR series (maleic anhydride modified EEA (product of Mitsui-DuPont Polychemicals)), Bondine (maleic anhydride modified EEA (product of Atopina)), Turftec (maleic anhydride modified SEBS, M1943 (product of Asahi Kasei), Clayton (maleic anhydride modified SEBS, FG1901X (product of Clayton Polymer)), Turfpren (maleic anhydride modified SBS, 912 (product of Asahi Kasei)), Septon (maleic anhydride modified SEPS (product of Kuraray)), Rexpearl (maleic anhydride modified EEA, ET-182G, 224M, 234M (product of Nippon Polyolefin)), and Aurorene (maleic anhydride modified EEA, 200S, 250S (product of Nippon Paper Chemical)). there is.

[0204] Examples of commercially available acid-unmodified thermoplastic elastomers (IV-B-2Y) include ethylene methacrylic acid copolymers such as Nuquerel (product of Mitsui DuPont Polychemical); ethylene methacrylic acid copolymers such as Eucaron (product of Mitsubishi Chemical); α-olefin copolymers such as Tuffmer (product of Mitsui Chemical); SEBS such as Tufftac (product of Asahi Chemical); SBS such as Tufffren (product of Asahi Chemical); SEPS such as Septon (product of Kuraray); and EEA such as Rexpearl (product of Nippon Polyolefin).

[0205] A particularly preferred example of an acid-modified thermoplastic elastomer (iv-b-2x) is a maleic anhydride-modified styrene-ethylene-butadiene-styrene copolymer. Commercially available acid-modified styrene-ethylene-butylene-styrene block copolymers include Asahi Kasei Chemicals’ Toughtac M1911: acid value 2 mgCH3ONa / g, MFR 4.5 g / 10 min, and Asahi Kasei Chemicals’ Toughtac M1913. Examples include: acid value 10 mg CH3ONa / g, MFR 5.0 g / 10 min, Tough Tec M1943 manufactured by Asahi Kasei Chemicals: acid value 10 mg CH3ONa / g, MFR 8.0 g / 10 min, etc.

[0206] Since the thermoplastic elastomer (iv-b-2) can increase the impact strength of the resulting r-CFRP, it is preferable that the Charpy impact strength measured according to JIS K7111-1 be 20 kJ / m² or higher, and more preferable that it be 30 kJ / m² or higher. The upper limit of the Charpy impact strength of the thermoplastic elastomer (iv-b-2) is not particularly limited, and one that does not fracture can be suitably used.

[0207] The average MFR of the thermoplastic elastomer (iv-b-2) is preferably 1.0 g / 10 min or more, and more preferably 5.0 g / 10 min or more. Since the average MFR of the thermoplastic elastomer (iv-b-2) is within the above range, the melt viscosity during processing is reduced, and fiber breakage of r-CF (A) due to processing can be suppressed, thereby enabling the expression of high physical properties.

[0208] The amount of thermoplastic elastomer (iv-b-2) is preferably 5 to 20 parts by mass with respect to 100 parts by mass of the thermoplastic resin composition to further improve the compatibility of elastic modulus and impact strength, more preferably 5 to 15 parts by mass, and even more preferably 5 to 10 parts by mass.

[0209] The amount of thermoplastic elastomer (iv-b-2) in the formulation is preferably 3 to 30 mass% of the thermoplastic resin (B) in 100 mass%, more preferably 5 to 25 mass%, and even more preferably 7 to 20 mass%. By having the amount of thermoplastic elastomer (iv-b-2) in the thermoplastic resin (B) within the above range, the impact strength and load bending temperature can be more compatible.

[0210] When acid-modified polypropylene (iv-b-1) and thermoplastic elastomer (iv-b-2) are included, the total content of acid-modified polypropylene (iv-b-1) and thermoplastic elastomer (iv-b-2) is preferably 3 to 30 parts by mass, more preferably 5 to 25 parts by mass, and even more preferably 7 to 20 parts by mass, with respect to 100 parts by mass of polyolefin resin having a melting point of 100°C or higher, because high physical properties can be achieved in strength, impact strength, and load bending temperature.

[0211] When acid-modified polypropylene (iv-b-1) and thermoplastic elastomer (iv-b-2) are included, the amount of acid-modified polypropylene (iv-b-1) is preferably 3 to 30 mass%, more preferably 5 to 25 mass%, and even more preferably 7 to 20 mass% of 100 mass% of thermoplastic resin (B), because high physical properties can be achieved in strength, impact strength, and load bending temperature. In addition, at this time, the amount of thermoplastic elastomer (iv-b-2) is preferably 3 to 25 mass%, more preferably 5 to 20 mass%, and even more preferably 7 to 15 mass%.

[0212] 4-1c. Arbitrary component

[0213] Any component of the present composition is omitted by referring to the description of any component in 1-1c above.

[0214] 4-2. Method for manufacturing a thermoplastic resin composition

[0215] The method for manufacturing the present composition is omitted by utilizing the description of the method for manufacturing the thermoplastic resin composition of 1-2 above.

[0216] 4-3. Molded body

[0217] The description of the molded body according to the fourth embodiment is omitted by referring to the description of the molded body of 1-3 above.

[0218] Example of implementation

[0219] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples. Additionally, items for which numerical values ​​are not listed in the table indicate that they are not contained.

[0220] "measurement method"

[0221] The physical properties of each raw material, example, reference example, and comparative example (hereinafter referred to as examples, etc.) were measured by the following method.

[0222] 1) Measurement of oxygen content in recycled carbon fibers

[0223] The oxygen content of r-CF(A) was measured using an energy-dispersive X-ray spectrometer attached to a scanning electron microscope (SEM) at an acceleration voltage of 15 kV and a field of view magnification of 3000x.

[0224] 2) Measurement of average solubility parameters of thermoplastic resin (B), etc.

[0225] The solubility parameter of the thermoplastic resin was calculated by Fedor's method. Specifically, based on the description in Polym. Eng. Sci., vol. 14, p. 147 (1974), it was calculated by the following formula (1).

[0226] Equation (1): SP value = √(Ev / v) = √(ΣΔei / ΣΔvi)

[0227] (In the formula, Ev: evaporation energy (cal / mol), v: molar volume (cm²) 3 / mol), Δei: evaporation energy of each atom or atomic group, Δvi: molar volume of each atom or atomic group)

[0228] 3) Measurement of diffraction intensities (I1) (2θ=25°) and (I2) (2θ=44°) of r-CF(A), etc.

[0229] Using an XRD (X-ray Diffractometer), Cu-Kα was used as a source, and the diffraction intensity of r-CF, ground into powder form, at 5° < 2θ < 110° was measured.

[0230] 4) Measurement of bulk density of r-CF(A), etc.

[0231] The bulk density of r-CF(A), etc., was measured in accordance with JIS K5101.

[0232] 5) Measurement of average MFR of thermoplastic resin (B), etc.

[0233] The MFR of thermoplastic resin (B), etc., was measured in accordance with JIS K7210-1.

[0234] 6) Measurement of Charpy impact strength of thermoplastic resin (B), etc. and molded body

[0235] The Charpy impact strength of the acid-modified thermoplastic elastomer (b-1) and the molded body was measured in accordance with JIS K7111-1.

[0236] 7) Measurement of glass transition temperature of thermoplastic resin (B), etc.

[0237] The glass transition temperature of a thermoplastic resin (B), etc. was measured using a differential scanning calorimeter (DSC) in accordance with JIS K7121:2012.

[0238] 8) Measurement of the acid value of recycled carbon fiber

[0239] To determine the acid value of r-CF(A), accurately weigh approximately 1 g of the sample into an orbicular conical flask and add 100 ml of a toluene / ethanol mixture (volume ratio: toluene / ethanol = 2 / 1), then stir. Add phenolphthalein solution as an indicator and maintain for 30 seconds. Subsequently, titrate with 0.1 N alcoholic potassium hydroxide solution until the solution turns pale pink. The acid value was calculated using the following formula (Unit: mgKOH / g).

[0240] Acid value (mgKOH / g) = {(5.611×a×F) / S} / (non-volatile concentration / 100)

[0241] Note, S: Amount of sample taken (g)

[0242] a: Consumption of 0.1N alcoholic potassium hydroxide solution (mL)

[0243] F: Titer of 0.1N alcoholic potassium hydroxide solution

[0244] 9) Measurement of flow onset temperature of thermoplastic resin (B), etc.

[0245] In accordance with JIS K7210, the flow initiation temperature was measured using a flow tester. Specifically, using a thermal fluidity evaluation device CFT-500D (manufactured by Shimadzu Corporation), the temperature at which the melt viscosity of the thermoplastic resin becomes 4800 Pa·s or less when passed through a capillary tube with a die hole diameter of φ1 mm and a die length of 1 mm under a pressure of 9.8 MPa was defined as the flow initiation temperature.

[0246] 10) Measurement of melt viscosity of acid-modified polypropylene (iv-b-1)

[0247] According to JIS K7199: 1999, a shear rate of 1.2×10 at 220℃ 3 sec -1 The melt viscosity of acid-modified polypropylene (iv-b-1) was measured.

[0248] 11) Measurement of the acid value of acid-modified polypropylene (iv-b-1)

[0249] The acid value of acid-modified polypropylene (iv-b-1) was measured according to JIS K-0070.

[0250] 12) Measurement of melting points of polyolefin resin (iv-B) and acid-modified polypropylene (iv-b-1)

[0251] The melting points of polyolefin resin (iv-B) and acid-modified polypropylene (iv-b-1) were measured using a differential scanning calorimeter DSC6200 (manufactured by Seiko Instruments) at a temperature range of 40 to 200°C and a heating rate of 10°C / min.

[0252] [1st Example]

[0253] Hereinafter, a first embodiment corresponding to the first embodiment will be described.

[0254] <r-CF의 제조>

[0255] 《Preparation Example 1-1》

[0256] CFRP derived from aircraft end material was heat-treated for 4 hours under a heated steam atmosphere at 750°C. Subsequently, recycled carbon fiber lumps were obtained by heat-treating at 550°C for 6 hours under air. The obtained recycled carbon fiber lumps were crushed with a cutter, and fibers of 4 to 15 mm were recovered to obtain the recycled carbon fiber r-CF-A according to Preparation Example 1.

[0257] 《Preparation Example 1-2》

[0258] Regenerated carbon fiber r-CF-B according to Preparation Example 2 was obtained by the same method as Preparation Example 1, except that the CFRP derived from aircraft parts was changed to CFRP derived from automotive parts waste.

[0259] 《Preparation Example 1-3》

[0260] Regenerated carbon fiber r-CF-C according to Preparation Example 3 is obtained using the same materials and manufacturing method as Preparation Example 1, except that the process of crushing with a cutter is not performed and the process of crushing with a grinder is performed.

[0261] 《Raw Materials》The raw materials used in the examples, etc. are shown below.

[0262] <r-CF(A) 등>

[0263] ·AI: r-CF-A (oxygen content 6 mass%, I1 / I2=5.8, bulk density 0.25 g / cm³) 3 )

[0264] ·A-II: r-CF-B (oxygen content 6 mass%, I1 / I2=5.0, bulk density 0.10 g / cm³) 3 )

[0265] ·A-III: r-CF-C (oxygen content 6 mass%, I1 / I2=5.9, bulk density 0.03 g / cm³) 3 )

[0266] ·A'-IV: v-CF-A (Mitsubishi Chemical product, oxygen content 0 mass%, I1 / I2=6.9, bulk density 0.53 g / cm³) 3 )

[0267] <Thermoplastic resin (B), etc.>

[0268] ·iBI: PA-6, Amylan CM1041-LO (Toray product, solubility parameter 11.6)

[0269] ·i- B-II: PA-66, Amylan CM3001N (Toray product, solubility parameter 13.6)

[0270] ·B'-I: PP, PMA60Z (PP resin, Sunallomer product, solubility parameter 9.3, glass transition temperature: 0℃, MFR 45g / 10 min)

[0271] [Acid-modified thermoplastic elastomer (b-1) etc.]

[0272] ·b-1-I: Acid-modified SEBS, Toughtac M1943 (Product of Asahi Kasei Chemicals, Acid value 10 mgCH3ONa / g, Glass transition temperature: -40℃, MFR 8.0 g / 10 min)

[0273] ·b'-1-II: SEBS, Toughtec H1221 (Product of Asahi Kasei Chemicals, MFR 5g / 10 min, Glass transition temperature: -42℃, No acid denaturation)

[0274] <Preparation of Thermoplastic Resin Composition>

[0275] (Example 1-1)

[0276] 10 parts by mass of AI as r-CF (A) and 90 parts by mass of iBI as thermoplastic resin (B) were used, and the mixture was extruded at 280°C using a twin-screw extruder (manufactured by Nippon Steel Co., Ltd.) to form granules, thereby obtaining a thermoplastic resin composition (see Table 1). Table 2 shows the physical properties of r-CF (A) and the thermoplastic resin (B).

[0277] (Examples 1-2 to 1-13, Reference Example 1-1, Comparative Example 1-1)

[0278] Thermoplastic resin compositions were each obtained in the same manner as in Example 1-1, except that the materials and mixing amounts (parts by mass) shown in Table 1 were changed respectively. Table 2 shows the physical property values ​​of r-CF (A) and thermoplastic resin (B) of each example, etc.

[0279] [Table 1]

[0280]

[0281] [Table 2]

[0282]

[0283] Evaluation of Thermoplastic Resin Compositions

[0284] The following evaluations were performed on the thermoplastic resin compositions according to each example, etc. The results are shown in Table 3.

[0285] α) Evaluation of productivity (deposits at the leading edge of the die)

[0286] When 2 kg of the thermoplastic resin composition of each example was produced at a discharge rate of 20 kg / h, the amount of deposits generated on the die at the tip of the extruder was evaluated according to the following criteria.

[0287] +++: Sediment weight less than 1g. Productivity is particularly good.

[0288] ++: Sediment weight is 1g or more and less than 3g. Good productivity.

[0289] +: Sediment weight is 3g or more and less than 5g. Productivity and practicality are possible.

[0290] NG: Sediment weight is 5g or more. Poor productivity.

[0291] β) Evaluation of productivity (fiber retention)

[0292] Likewise, regarding the fiber feedability when extruding the thermoplastic resin composition of each example, the state of fiber retention at the raw material feed port was visually evaluated when fibers were supplied at a discharge rate of 6 kg / h using a gravimetric feeder with a hopper capacity of 25 L.

[0293] +++: No dwell time. Productivity is particularly good.

[0294] ++ : Slight retention occurs. Good productivity.

[0295] +: Retention occurs to a degree that does not affect the extrusion process. Productivity is possible.

[0296] NG: Fiber not fed to the extruder due to retention. Poor productivity.

[0297] <Manufacturing of Molded Body>

[0298] The thermoplastic resin compositions of each example were molded using an injection molding machine (Toshiba Machinery Co. product) to obtain a multi-purpose test specimen with dimensions of 80 mm in length × 10 mm in width × 4 mm in thickness.

[0299] <Evaluation of the molded body>

[0300] The following evaluations were performed on the molded bodies according to each example, etc. The results are shown in Table 3.

[0301] γ) Evaluation of elastic modulus

[0302] The bending modulus was measured according to JIS K7171:2016 using multi-purpose test specimens obtained from each example. Higher measured values ​​indicated superior strength. The evaluation criteria for the modulus were as follows.

[0303] +++: 10,000 MPa or higher. Excellent.

[0304] ++: 8000MPa or higher, less than 10000MPa. Good.

[0305] +: 5000MPa or more, less than 8000MPa. Practical range.

[0306] NG: Less than 5000MPa. Defective.

[0307] δ) Evaluation of Charpy impact strength

[0308] Notched Charpy impact strength was measured according to JIS K7111-1:2012 using multi-purpose test specimens obtained from each example. The evaluation criteria were as follows.

[0309] +++: 15kJ / ㎡ or higher. Excellent.

[0310] ++: 7kJ / ㎡ or higher, less than 15kJ / ㎡. Good.

[0311] +: 5kJ / ㎡ or more, less than 7kJ / ㎡. Practically feasible range.

[0312] NG: Less than 5kJ / ㎡.

[0313] For applications requiring high strength, such as automotive parts, it is desirable to have a Charpy impact strength of 7 kJ / m² or higher.

[0314] [Table 3]

[0315]

[0316] As shown in the examples of Table 3, it was confirmed that a molded body formed from a thermoplastic resin composition combining r-CF (A) with an oxygen content of 5.0 mass% or more and a thermoplastic resin (B) with a solubility parameter of 10 to 15 had excellent productivity and excellent elastic modulus and impact strength.

[0317] [2nd Example]

[0318] Hereinafter, an embodiment corresponding to the second embodiment will be described.

[0319] <r-CF의 제조>

[0320] Preparation Examples 2-1 to 2-3

[0321] Preparation Examples 1-1 to 1-3 are used in order.

[0322] "raw material"

[0323] The raw materials used in the examples, etc. are shown below.

[0324] <r-CF(A) 등>

[0325] ·AI, A-II, A-III, and A'-IV are omitted and refer to the description of the first embodiment.

[0326] <Thermoplastic resin (B), etc.>

[0327] ·ii-B1-I: Acrypet TF-9 (PMMA resin, Mitsubishi Chemical, solubility parameter: 9.2, glass transition temperature: 90℃, MFR 20g / 10 min)

[0328] ·ii-B1-II: Acrypet VH-3F (PMMA resin, Mitsubishi Chemical, solubility parameter: 9.5, glass transition temperature: 90℃, MFR 1.8g / 10 min)

[0329] ·ii-B2a-I: Sebian T-500SF (ABS resin, manufactured by Daicel Miraise, solubility parameter: 9.6, glass transition temperature: 80℃, MFR 25g / 10 min)

[0330] ·ii-B2a-II: Sebian 466MD (ABS resin, manufactured by Daicel Miraise, solubility parameter: 9.9, glass transition temperature: 95℃, MFR 4.0g / 10 min)

[0331] ·ii-B2b-I: Sebian 090SF (AS resin, manufactured by Daicel Miraise, solubility parameter: 10.0, glass transition temperature: 100℃, MFR 23g / 10 min)

[0332] ·ii-B2b-II: Sunrex SAN-H (AS resin, Techno UMG product, solubility parameter: 10.7, glass transition temperature: 105℃, MFR 5.0g / 10min)

[0333] ·B '-I : The description of the first embodiment is adopted and omitted.

[0334] [Acid-modified thermoplastic elastomer (b-1) etc.]

[0335] b-1-I and b'-1-II are omitted and refer to the description of the first embodiment.

[0336] <Preparation of Thermoplastic Resin Composition>

[0337] (Example 2-1)

[0338] A thermoplastic resin composition was obtained by using 10 parts by mass of AI as r-CF (A) and 90 parts by mass of ii-B1-I as thermoplastic resin (B), extruding at 280°C using a twin-screw extruder (manufactured by Nippon Steel Co., Ltd.), and granulating (see Table 4). Table 7 shows the physical properties of r-CF (A) and thermoplastic resin (B).

[0339] (Examples 2-2 to 2-36, Reference Examples 2-1 to 2-3, Comparative Example 2-1)

[0340] Thermoplastic resin compositions were each obtained in the same manner as in Example 2-1, except that the materials and mixing amounts (parts by mass) shown in Tables 4 to 6 were changed, respectively. Tables 7 to 9 show the physical property values ​​of r-CF (A) and thermoplastic resin (B) of each example, etc.

[0341] [Table 4]

[0342]

[0343] [Table 5]

[0344]

[0345] [Table 6]

[0346]

[0347] [Table 7]

[0348]

[0349] [Table 8]

[0350]

[0351] [Table 9]

[0352]

[0353] Evaluation of Thermoplastic Resin Compositions

[0354] The evaluation method is based on the description of the first embodiment. The results are shown in Tables 10 to 12.

[0355] [Table 10]

[0356]

[0357] [Table 11]

[0358]

[0359] [Table 12]

[0360]

[0361] As shown in the examples of Tables 10 to 12, it was confirmed that a molded body formed from a thermoplastic resin composition combining r-CF (A) with an oxygen content of 5.0 mass% or more and a thermoplastic resin (B) with a solubility parameter of 9 to 15 had excellent productivity and excellent elastic modulus and impact strength.

[0362] [3rd Example]

[0363] Hereinafter, a third embodiment corresponding to the third embodiment will be described.

[0364] <r-CF의 제조>

[0365] Preparation Examples 3-1 to 3-3

[0366] Preparation Examples 1-1 to 1-3 are used in order.

[0367] 《Preparation Example 3-4》

[0368] r-CF-D was obtained by heat-treating CFRP derived from aircraft parts at 450°C to remove resin components, then performing a 3V DC electrolytic reaction under an aqueous sodium hydroxide solution with the anode being a carbon fiber aggregate and the cathode being a titanium electrode, and crushing and classifying the resulting recycled carbon fiber lumps with a crusher.

[0369] "raw material"

[0370] The raw materials used in the examples, etc. are shown below.

[0371] <r-CF(A) 등>

[0372] ·AV: r-CF-E (oxygen content 6 mass%, acid value 0.060 mmol / g, I1 / I2=5.8, bulk density 0.25 g / cm³ 3 )

[0373] ·A-VI: r-CF-F (oxygen content 6 mass%, acid value 0.004 mmol / g, I1 / I2=5.0, bulk density 0.10 g / cm³ 3 )

[0374] ·A-VII: r-CF-G (oxygen content 6 mass%, acid value 0.060 mmol / g, I1 / I2=5.9, bulk density 0.03 g / cm³)

[0375] ·A-VIII: r-CF-H (oxygen content 8 mass%, acid value 0.120 mmol / g, I1 / I2=4.9, bulk density 0.23 g / cm³ 3 )

[0376] ·A'-II: v-CF-B (Mitsubishi Chemical product, oxygen content 0 mass%, acid value 0.001 mmol / g, I1 / I2=6.9, bulk density 0.53 g / cm³) 3 )

[0377] <Thermoplastic resin (B), etc.>

[0378] ·iii-B1-I: Torecon 1401×06 (Toray product, PBT (polyester resin), flow onset temperature: 224℃)

[0379] ·iii-B1-II: Tritan GN071 (Eastman Chemicals product, PET-G (polyester resin), flow onset temperature: 235℃)

[0380] ·iii-B2-I: Upyron E-2000 (Mitsubishi Engineering Plastics product, PC (polycarbonate resin), flow onset temperature: 230℃)

[0381] ·iii-B2-II: Novaloy S1500 (Daicel Polymer, PC (Polycarbonate Resin), Flow On Temperature: 220℃)

[0382] ·iii-B1-III: Mitsui PET SA135 (Mitsui Chemicals, PET (polyester resin), flow onset temperature: 253℃)

[0383] ·B'-II: Sunallomer PMA-60Z (Sunallomer product, PP (polypropylene resin), flow onset temperature: 140℃)

[0384] [Acid-modified thermoplastic elastomer (b-1) etc.]

[0385] b-1-I incorporates the description of the first embodiment.

[0386] <Preparation of Thermoplastic Resin Composition>

[0387] (Example 3-1)

[0388] A thermoplastic resin composition was obtained by using 10 parts by mass of AV as r-CF (A) and 90 parts by mass of iii-B1-I as thermoplastic resin (B), extruding at 280°C using a twin-screw extruder (manufactured by Nippon Steel Co., Ltd.), and granulating (see Table 13). Table 14 shows the physical properties of r-CF (A) and thermoplastic resin (B).

[0389] (Examples 3-2 to 3-20, Reference Example 3-1, Comparative Examples 3-1 to 3-4)

[0390] Thermoplastic resin compositions were each obtained in the same manner as in Example 3-1, except that the materials and mixing amounts (parts by mass) shown in Table 13 were changed respectively. Table 14 shows the physical property values ​​of r-CF (A) and thermoplastic resin (B) of each example, etc.

[0391] [Table 13]

[0392]

[0393] [Table 14]

[0394]

[0395] Evaluation of Thermoplastic Resin Compositions

[0396] The evaluation method is based on the description of the example for the first embodiment. The results are shown in Table 15.

[0397] [Table 15]

[0398]

[0399] As shown in the examples of Table 15, a molded body formed from a thermoplastic resin composition for carbon fiber reinforcement containing recycled carbon fiber (A) and a thermoplastic resin (B) was found to have excellent productivity and excellent elastic modulus and impact strength. In the example, the recycled carbon fiber (A) has an oxygen content of 5.0 mass% or more and an acid value of 0.002 to 0.080 mmol / g, and the thermoplastic resin (B) has an average flow initiation temperature of 250°C or less and includes at least one of a polyester resin (iii-B1) and a polycarbonate resin (iii-B2).

[0400] [Fourth Example]

[0401] Hereinafter, a fourth embodiment corresponding to the fourth embodiment will be described.

[0402] <r-CF의 제조>

[0403] Preparation Examples 4-1 to 4-3

[0404] Preparation Examples 1-1 to 1-3 are used in order.

[0405] "raw material"

[0406] The raw materials used in the examples, etc. are shown below.

[0407] <r-CF(A) 등>

[0408] The same AI to A-III and A'-IV as in the first embodiment were used.

[0409] <Thermoplastic resin (B)>

[0410] ·iv-BI: Prime PolyPro J708UG (Sunallomer product, melting point 162℃, block PP, MFR 45g / 10 min)

[0411] ·iv-B-II: Prime Polypro E-200GP (Prime Polymer product, melting point 165℃, homo PP, MFR 2.0g / 10 min)

[0412] ·iv-B-III: SunAllomer PM900A (SunAllomer product, homopropyl PP, melting point 163℃, MFR 30g / 10 min)

[0413] [Acid-modified polypropylene (iv-b-1), etc.]

[0414] ·iv-b-1-I: Admer QB550 (Mitsui Chemicals, melting viscosity 200 MPa·s, acid value 2.3 mg KOH / g, melting point: 165℃)

[0415] ·iv-b-1-II: UMEX 1001 (manufactured by Sanyo Chemical, melting viscosity 1 MPa·s, acid value 26 mgKOH / g, melting point: 142℃)

[0416] [Thermoplastic elastomer (b-2) etc.]

[0417] · iv-b-2x-I: Acid-modified SEBS, Toughtec M1943 (Product of Asahi Kasei Chemicals, Acid value 10 mgCH3ONa / g, MFR 8.0 g / 10 min)

[0418] · iv-b-2y-II: SEBS, Toughtec H1221 (Asahi Kasei Chemicals, MFR 5.0g / 10 min, no acid denaturation)

[0419] · iv-b-2x-III: Acid-modified ethylene-propylene rubber, toughmer MP0610 (Mitsui Chemicals, MFR 0.6g / 10 min)

[0420] · iv-b-2y-IV: Ethylene-propylene rubber, toughmer DF640 (Mitsui Chemicals product, MFR 3.6g / 10 min, no acid modification)

[0421] <Preparation of Thermoplastic Resin Composition>

[0422] (Example 4-1)

[0423] A thermoplastic resin composition was obtained by extruding 10 parts by mass of AI as r-CF (A), 87 parts by mass of polyolefin resin (iv-B) as thermoplastic resin (B), and 3 parts by mass of acid-modified polypropylene (iv-b-1-I) using a twin-screw extruder (manufactured by Nippon Steel Co., Ltd.) at 280°C and granulating them (see Table 16). Table 18 shows the physical properties of r-CF (A) and the thermoplastic resin (B).

[0424] (Examples 4-2 to 4-33, Reference Examples 4-1, 4-2, Comparative Example 4-1)

[0425] Thermoplastic resin compositions were each obtained in the same manner as in Example 4-1, except that the materials and mixing amounts (parts by mass) were changed to those shown in Tables 16 and 17, respectively. Tables 18 and 19 show the physical property values ​​of r-CF (A) and thermoplastic resin (B) of each example, etc.

[0426] [Table 16]

[0427]

[0428] [Table 17]

[0429]

[0430] [Table 18]

[0431]

[0432] [Table 19]

[0433]

[0434] Evaluation of Thermoplastic Resin Compositions

[0435] The following evaluations were performed on the thermoplastic resin compositions according to each example, etc. The results are shown in Tables 20 and 21.

[0436] For α) evaluation of productivity (deposit at the tip of the die) and β) evaluation of productivity (retention of fibers), the first embodiment is used.

[0437] <Manufacturing of Molded Body>

[0438] The thermoplastic resin compositions of each example were molded using an injection molding machine (a product of Toshiba Machinery Co., Ltd.) to obtain a dumbbell-shaped test specimen of type A1 and a strip-shaped test specimen of type B2 in accordance with JIS K7139:2019.

[0439] <Evaluation of the molded body>

[0440] The following evaluations were performed on the molded bodies according to each example, etc. The results are shown in Tables 20 and 21.

[0441] γ) Evaluation of tensile strength

[0442] Tensile strength was measured according to JIS K7161-1:2014 using dumbbell-shaped test specimens obtained from each example. A higher measured value indicates superior tensile strength. The evaluation criteria for strength were as follows.

[0443] +++: 80MPa or higher. Excellent.

[0444] ++: 60MPa or higher, less than 80MPa. Good.

[0445] +: 40MPa or more, less than 60MPa. Practical range.

[0446] NG: Less than 40MPa. Defective.

[0447] For applications requiring high strength, such as automotive parts, it is desirable to have a tensile strength of 60 MPa or higher.

[0448] δ) Evaluation of elastic modulus and ε) Evaluation of Charpy impact strength were evaluated using the same method and criteria as in the first embodiment, except that the molding method was different as described above.

[0449] ζ) Evaluation of Load-Bending Temperature (HDT)

[0450] Using the strip-type test specimens obtained in each example, the load bending temperature was measured according to JIS K7191-2: 2015. The evaluation criteria were as follows.

[0451] +++: 140℃ or higher. Excellent.

[0452] ++: 120℃ or higher, less than 140℃. Good.

[0453] +: 100℃ or higher, less than 120℃. Practical range.

[0454] NG: Below 100℃.

[0455] For applications requiring high heat resistance, such as automotive parts, it is desirable that the load bending temperature be 120°C or higher.

[0456] [Table 20]

[0457]

[0458] [Table 21]

[0459]

[0460] As shown in the examples of Tables 20 and 21, it was confirmed that a molded body formed from a thermoplastic resin composition combining r-CF (A) with an oxygen content of 5.0 mass% or more; a polyolefin resin (iv-B); and at least one of acid-modified polypropylene (iv-b-1) and a thermoplastic elastomer (iv-b-2) had excellent productivity and excellent tensile strength, elastic modulus, impact strength, and load bending temperature.

[0461] Industrial applicability

[0462] According to the present invention, even when recycled carbon fibers are used, a thermoplastic resin composition and a molded article comprising recycled carbon fibers with excellent productivity and impact resistance can be provided, so they can be used as recycled carbon fiber reinforced plastics.

[0463] This application claims priority based on Japanese application No. 2021-93138 filed on June 2, 2021, Japanese application No. 2021-190760, Japanese application No. 2021-190761 and Japanese application No. 2021-190762 filed on November 25, 2021, and Japanese application No. 2021-198686 filed on December 7, 2021, and the entire disclosure thereof is incorporated herein.

Claims

Claim 1 A thermoplastic resin composition for carbon fiber reinforcement containing recycled carbon fiber (A) and a thermoplastic resin (B), wherein the oxygen content in the recycled carbon fiber (A) is 5.0 mass% or more and satisfies any one of the following (i) to (iv): (i): the thermoplastic resin (B) has an average solubility parameter of 10 to 15 and also includes a polyamide resin (iB); (ii): the thermoplastic resin (B) has an average solubility parameter of 9 to 15 and also includes at least one of an acrylic resin (ii-B1) and a styrene resin (ii-B2), and said acrylic resin (ii-B1) and styrene resin (ii-B2) have a glass transition temperature of 0°C or higher; (iii): the acid value of the recycled carbon fiber (A) is 0.002 to 0.080 mmol / g and the thermoplastic resin (B) has an average flow onset temperature of 250°C The above includes at least one of a polyester resin (iii-B1) and a polycarbonate resin (iii-B2), (iv): the thermoplastic resin (B) comprises a polyolefin resin having a melting point of 100°C or higher (except in the case of an acid-modified thermoplastic resin) (iv-B), and at least one of an acid-modified polypropylene (iv-b-1) and a thermoplastic elastomer (iv-b-2), wherein the melting point of the acid-modified polypropylene (iv-b-1) is 130°C or higher, provided that the oxygen content is a value obtained when measuring using an energy-dispersive X-ray spectrometer attached to a scanning electron microscope (SEM) at an acceleration voltage of 15 kV and a field of view magnification of 3000x, and the average solubility parameter is given by the following formula (1): SP value = √(Ev / v) = √(ΣΔei / ΣΔvi) (wherein, Ev: evaporation energy (cal / mol), v: Molar volume (cm²) 3 A thermoplastic resin composition, wherein the flow initiation temperature is a value calculated by Δei: evaporation energy of each atom or group of atoms, and Δvi: molar volume of each atom or group of atoms, and wherein, in the evaluation of melt viscosity by a flow tester, the melt viscosity of the thermoplastic resin becomes 4800 Pa·s or less under a pressure of 9.8 MPa. Claim 2 A thermoplastic resin composition according to claim 1, characterized in that the ratio (I1 / I2) of the diffraction intensity (I1) at a Bragg angle 2θ=25° and the diffraction intensity (I2) at 2θ=44° observed by X-ray diffraction of the regenerated carbon fiber (A) is less than 6. Claim 3 A thermoplastic resin composition according to claim 1, characterized in that the bulk density of the recycled carbon fiber (A) is 0.03 to 1.0 g / cm³, provided that the bulk density is a value obtained in accordance with JIS K5101. Claim 4 In claim 1, satisfying (iv), the acid-modified polypropylene (iv-b-1) is at 220°C and a shear rate of 1.2×10⁻⁶ 3 sec -1 The melting viscosity (ηc) at A thermoplastic resin composition characterized by having a strength of 10 to 500 Pa·s. Claim 5 A thermoplastic resin composition according to claim 1, wherein (iv) satisfies (iv) and has a melting point of 100°C or higher (except in cases where it is an acid-modified thermoplastic resin), and (iv-B) is a homopolymer of polypropylene. Claim 6 A thermoplastic resin composition satisfying (iv) in claim 1, wherein the thermoplastic resin (B) comprises acid-modified polypropylene (iv-b-1) and a thermoplastic elastomer (iv-b-2). Claim 7 A thermoplastic resin composition according to claim 1, satisfying any one of (i) to (iii), wherein the thermoplastic resin (B) comprises an acid-modified thermoplastic elastomer (b-1). Claim 8 A molded body formed by molding from a thermoplastic resin composition according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Recovered carbon fiber reinforced polypropylene composite material and preparation method thereof

    CN103571036A

  • Carbon fiber-reinforced polyester resin, and method for manufacturing injection molded object thereof

    JP2016041800A

  • Fiber Reinforced Polymer Composition

    JP2018517014A

  • Carbon fiber composite material containing recycled carbon fibers, molded body, and method for producing carbon fiber composite material

    WO2020235533A1